METODE PELAKSANAAN PEKERJAAN LANTAI PARTISI DI SALURAN INDUK CIPELANG PADA RENTANG IRRIGATION MODERNIZATION PROJECT - Sunarya, Yoyo; Juliar, Eka (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
The Range Irrigation Area is a national strategic project located in the lowlands of the lower reaches of the Cimanuk River in the Northeastern part of West Java Province. The modernization of Span Irrigation is carried out because the age of the irrigation system is decaded old, causing reduced water service performance due to narrowing of the enbankments, sediment and groundwater infiltration in the Cipelang Main Canal. The use of material for contruction that is on the ground surface of this irrigation canal is by using a concrete floor (partition floor) which aims to reduce the water loss factor in the Cipelang Main Canal. The techninal work for making concrete floors is carried out in a Cast In Site manner, meaning the type of concrete casting work on site or directly in the workplace. The Partition Concrete Floor work in the Cipelang main canal aims to reduce the water loss factor so that it can increase the efficiency of irrigation water use. Partition Concrete Floor use K-175 concrete quality with cast in site technical work, not using precast concrete. There are 9 (nine) stages regarding the Partition Floor Work Implementation Method, namely starting from the work of Preparation, Kisdam, Dewatering, Excavation + Furnishing and Installation Filter, Lean Concrete Floor, Wiremesh + Install Beam and Footing Reinsforcement, Casting In Site, Finishing Top Floor, Concrete Curing.